Support Teacher as Key Factor of Integration Children with Special Education Needs in Mainstream School - Voinea, Mihaela; Topală, Ioana Roxana (European Journal of Social Science Education and Research, 2021)
The issue of integrating children with special educational needs in mainstream school depends on several factors. The most important is the support teacher, who is the link between school, family and community, between children and teachers and other specialists. (Avramidis - all 2000, Ainscow 2016, etc.). Teachers need to change their own mind set and system of values according to the new social responsibilities in order to become promoters of human diversity, acceptance and tolerance. Therefore, teacher training must respond diligently to the new teacher’s roles and responsibilities. The main purpose of this research was to identify the training needs for support teachers based on the analysis of their own socio-educational experience (their own role and their particular training needs as support teachers), as well as (mainstream school) teachers’, pupils’ and parents’ perceptions regarding integration. This study was conducted in a mixt methods structure, which employed both quantitative and qualitative methods for data collection. A questionnaire-based survey was conducted, with mainstream teachers, on one hand, and parents, on the other hand. We addressed the issues of attitudes towards the integration of children with SEN (special education needs) and the collaboration with the support teacher. Also, focus-group interviews were conducted with support teachers. A number of 112 participants were included in the study (57 teachers from mainstream schools, 20 support teachers, and 35 parents ) Conclusion: Teachers’ and parents’ cognitive schemas regarding what a support teacher can and should do in order to facilitate the integration of children with SEN are different from his/her actual educational role and responsibilities. This gap between the social representations and the actual job description can be bridged by building a more complex and accurate understanding of how every actor involved in the integration process must become aware of one’s personal beliefs and expectations, assume and thoroughly play his/her part in a collaborative manner. Teacher training through transformative learning based on sharing experiences and group projects is a learning experience suitable for developing competences for teachers for special education.Keywords: teacher training, children with special educational needs, transformative learning, support teacher.